Solar‐powered flow‐through system for aquatic field studies. Issue 12 (26th June 2017) - Neill, Connor; Cotner, Sehoya; Wisenden, Brian
Abstract: Laboratory‐based research provides great control over individual experimental replicates, but lacks the ecological realism of field work. Therefore, results from laboratory‐based work may not reflect natural processes. Field‐based studies have the advantage of ecological realism but often lack control over environmental variables and have low rates of within‐experiment replication and as a result can have low statistical power to detect effects. Here, we present a method for creating a standardized system for experimental replicates in the field using solar‐powered water pumps to run a modified zebrafish aquatic habitat system with recirculating water in situ. In our pilot study we used this apparatus to test the effects of naturally occurring parasites on the behaviour of individual fathead minnows, but this experimental set‐up has potential for broad application to field‐based research in aquatic ecology. We constructed a simple frame from conventional 2″ × 4″ lumber to support rows of 1‐L tanks in the littoral zone of a small lake. Lake water is pumped to an overhead manifold made from a PVC pipe drilled with one hole over each tank. A short length of airline tubing directs the water flow into each individual tank. Water entering each tank passes through the manufacturer's grate at the rear of each tank and returns to the lake. We stocked one fish per tank, therefore the lack of water flow during the night did not cause duress or mortality. This system allowed control over individual test subjects while housing them in semi‐natural conditions with a steady supply of lake water at a field site far removed from any source of electricity.